2021
DOI: 10.4414/smw.2021.w30024
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Physician Workforce 2020 to 2025 – a cross-sectional study for the Canton of Bern

Abstract: AIM OF THIS STUDY: The Swiss primary care sector faces a lack in its workforce and the Canton of Bern - the second largest canton (i.e. federal state) – is believed to be more affected than others. To be able to predict a shortage in the overall workforce, reliable numbers for the workforce of all general practitioners (GPs) and paediatricians (primary care physicians, PCPs) actively working in the Canton of Bern are needed. Switzerland has no registry of active PCPs; therefore, our goal was to (1) define the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 0 publications
0
0
0
3
Order By: Relevance
“…A nationwide longitudinal study in Hungary observed a decrease in GP practices by 7.7% between 2007 and 2016 [74]. These tendencies might ultimately lead to inequities in access to healthcare as well as shortages of medical services [74,77]. While family medicine is still a rewarding career for young residents, as it offers high autonomy in diverse work settings and long-term doctor-patient relationships, the design of workplaces and working conditions needs to respect the described associations to psychological well-being [78,79].…”
Section: Discussionmentioning
confidence: 99%
“…A nationwide longitudinal study in Hungary observed a decrease in GP practices by 7.7% between 2007 and 2016 [74]. These tendencies might ultimately lead to inequities in access to healthcare as well as shortages of medical services [74,77]. While family medicine is still a rewarding career for young residents, as it offers high autonomy in diverse work settings and long-term doctor-patient relationships, the design of workplaces and working conditions needs to respect the described associations to psychological well-being [78,79].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies (6/7) from the UK covered the entire Kingdom [38,46,47] or a select UK state, i.e., England [42,44] and Ireland [45], while 1 study was a case study conducted at the Nuffield Anaesthesiology Unit at John Radcliffe Hospital, Oxford [27]. The remaining eight empirical studies focused on various European countries, such as the Czech Republic [48], Germany [28], Greece [29,40], Lithuania [30,43], Switzerland [31], Spain [32], Malta [33], Hungary [34], and Italy [39], but three focused on select regions of individual countriesthe canton of Bern [31], Emilia-Romagna [39], and Hradec Kralove-in comparison with the entire Czech Republic [48]. Two theoretical papers focused on European countries [16,55] and one focused on the OECD states [9].…”
Section: Countries Covered In the Included Publicationsmentioning
confidence: 99%
“…Eine suffiziente Grundversorgung ist neben dem selbstverständlichen Gesundheitsaspekt auch von wirtschaftlichem Interesse, da Haus-und Kinderärzte 94,3% der Gesund-heitsprobleme abschliessend lösen und dabei nur 7,9% der Gesundheitskosten verursachen [9]. Um der aktuellen Unterversorgung von Praxispädiaterinnen und -pädiatern entgegenzuwirken, sind effizienzsteigernde oder die Arbeitszeit beschränkende Massnahmen bereits in der Assistenzzeit von Relevanz [10,11].…”
Section: Diskussionunclassified